Supervision and quality assurance policy for higher education in El Salvador: analysis of the results of the implementation of the institutional evaluation subsystem, period 1999-2011 - Escamilla, Cristela (Journal Studies of Public Policy, 2016)
The Ley de Educación Superior implementation in El Salvador, enacted in 1996, has internalized quality improvement process in higher education institutions. However, during the 15 years since the Law, there was no monitoring and evaluation system, which could analyze the progress of the quality. To have an updated assessment of the institutional analysis, three sources of information were studied: i) Resolutions issued by the Ministry of Education 1999-2011, ii) Academic quality indicators established in the Subsistema de Información y Estadísticas 1999-2011, and iii) Electronic consultation to Peer Evaluators about the effectiveness of the assurance quality policy. We concluded that the evaluation process was not delivering the expected results because the IES backslidid into the evaluator’s comments, especially in areas of research, social projection, educational resources and institutional integrity. We also noted that non-accredited universities had no progress in most quality indicators.